Synthesis and Characterization of Tripolyphosphate Chitosans through a Crosslinking Process from High Chemical Weight Chitosans - Jolantje Latupeirissa; Matheis F. J. D. P. Tanasale; Eirene G. Fransina; Nikmans Hattu; Semuel S. Pada; Helna Lourita Sopamena (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to synthesize and characterize chitosan-tripolyphosphate (CTPP) through ionic crosslinking between chitosan and sodium tripolyphosphate. The CTPP powder was characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and surface area analysis (BET), alongside solubility, swelling, and point of zero charge (pHZPC) tests. FTIR spectra showed a peak at 1151.5 cm⁻¹ attributed to P=O stretching, confirming the interaction between chitosan and tripolyphosphate. XRD analysis indicated shifts in diffraction peaks, suggesting a successful crosslinking reaction. SEM images revealed that the resulting particles had a compact and aggregated morphology. BET analysis showed a decrease in surface area compared to pure chitosan, which may be attributed to particle agglomeration upon crosslinking. Solubility tests revealed that while chitosan is soluble in acidic media, the CTPP product is insoluble. The CTPP showed a swelling percentage of 60% in acidic conditions, indicating its potential responsiveness. The pHZPC measurement indicated a value of 6.2, with ΔpH = 0, suggesting moderate surface charge behavior in neutral pH conditions. Overall, the study confirms the successful synthesis of crosslinked CTPP with distinct physicochemical properties suitable for further application development.